Kombinasi Tiga Algoritma Penjadwalan sebagai Upaya Meningkatkan Pelayanan Pelanggan pada Usaha Konveksi - Siti Mutrofin; M. Dimas Ghifari Muafah; Mas’ud; Ahmad Farhan (Jurnal Informasi dan Teknologi, 2022)
Konveksi Fariasi is a convection that focuses on the production of t-shirts in Jombang. The problem is experienced by Konveksi Fariasi is scheduling the production of customer order shirts based on the order of arrival time or First In First Serve (FCFS), where the first arrival will get the first service. FCFS is not profitable for customers who order a small number of t-shirts that are not included in the First or Initial queue, because they have to wait for previous queues which may have more orders in the front queue. FCFS does not benefit the ordering of t-shirts that are not in the first line even though the order is small. From these problems, the current production scheduling system needs to be optimized. In this study, the data used are ordering data for September 2017. The results of data analysis and business processes, this study propose a combination of three scheduling algorithms as a solution to improve customer service. The algorithm consists of Dynamic Priority, Shortest Job First (SJF) and First in First Serve (FCFS). Dynamic Priority is useful for customers who want to prioritize their orders, SJF is useful for small orders, FCFS is useful for sorting according to the earliest date of arrival. The trial results of the combination of the three algorithms show better results than just using FCFS. The average waiting time is 664 days for the combination of the three proposed algorithms, compared if only using the FCFS algorithm which is 747 days.